Characterization of a nucleocapsid-like region and of two distinct primer tRNA(Lys,2) binding sites in the endogenous retrovirus Gypsy - Gabus, Caroline (Oxford University Press, 2006)
Mobile LTR-retroelements comprising retroviruses and LTR-retrotransposons form a large part of eukaryotic genomes. Their mode of replication and abundance favour the notion that they are major actors in eukaryote evolution. The Gypsy retroelement can spread in the germ line of the fruit fly Drosophila melanogaster via both env-independent and env-dependent processes. Thus, Gypsy is both an active retrotransposon and an infectious retrovirus resembling the gammaretrovirus MuLV. However, unlike gammaretroviruses, the Gypsy Gag structural precursor is not processed into Matrix, Capsid and Nucleocapsid (NC) proteins. In contrast, it has features in common with Gag of the ancient yeast TY1 retroelement. These characteristics of Gypsy make it a very interesting model to study replication of a retroelement at the frontier between ancient retrotransposons and retroviruses. We investigated Gypsy replication using an in vitro model system and transfection of insect cells. Results show that an unstructured domain of Gypsy Gag has all the properties of a retroviral NC. This NC-like peptide forms ribonucleoparticle-like complexes upon binding Gypsy RNA and directs the annealing of primer tRNA(Lys,2) to two distinct primer binding sites (PBS) at the genome 5′ and 3′ ends. Only the 5′ PBS is indispensable for cDNA synthesis in vitro and in Drosophila cells.